Anti-Inflammatory Effects of Ginsenoside Rb3 in LPS-Induced Macrophages Through Direct Inhibition of TLR4 Signaling Pathway - Xu, Honglin; Liu, Min; Chen, Guanghong; Wu, Yuting; Xie, Lingpeng; Han, Xin; Zhang, Guoyong; Tan, Zhangbin; Ding, Wenjun; Fan, Huijie; Chen, Hongmei; Liu, Bin; et al. (Frontiers in Pharmacology, 2022)
Panax ginseng has therapeutic effects on various inflammation-related diseases. Ginsenoside Rb3 (GRb3), a natural compound with anti-inflammatory and immunomodulatory properties, is one of the main active panaxadiol extracted from panax ginseng. We explored whether GRb3 inhibited LPS-mediated inflammation through TLR4/NF-κB/MAPK signaling in macrophages. GRb3 attenuated NO and PGE2 production by attenuating iNOS and COX2 expression. GRb3 also suppressed pro-inflammatory cytokines levels, including IL-1β, IL-6, and TNF-α. Moreover, GRb3 administration significantly suppressed NF-κB (p65) nuclear translocation and the phosphorylation levels of p65, IκBα, JNK, p38, and ERK dose-dependently. Molecular docking demonstrated that GRb3 could dock onto the hydrophobic binding site of TLR4/MD2 complex, with a binding energy of -8.79 kcal/mol. Molecular dynamics (MD) displayed stable TLR4-MD2-GRb3 modeling. GRb3 dose-dependently inhibited LPS binding to cell membranes and blocked TLR4 expression. Surface plasmon resonance imaging (SPRi) revealed that GRb3 had an excellent binding affinity to TLR4/MD2 complex. Notably, Resatorvid (TAK242), a seletive TLR4 inhibitor, didn't increase the repressive influence of GRb3 in RAW264.7 macrophages. Moreover, TLR4 overexpression partially reversed the repressive roles of GRb3 on NF-κB/MAPK pathway and inflammatory mediators. Collectively, our study strongly indicated that GRb3 attenuate LPS-mediated inflammation through direct inhibition of TLR4 signaling. A novel insight into the underlying mechanism of anti-inflammatory effects of GRb3 in macrophages was confirmed.